A Key to Successful Business Retail - Oktarina, Rury Rosadi; wahyono, wahyono (Management Analysis Journal, 2019)
The key to the success of the retail business lies in the high purchase decision among consumers. The purpose of this study is to test partially and simultaneously the influence of lifestyle, merchandise assortment, and service quality on purchase decision through purchase intention. The population in this study were all unknown numbers of Giant Semarang customers. Sampling was done by nonprobability sampling technique that is incidental sampling, with a total sample of 115 respondents. Data collection methods used were documentation and questionnaires. Data analysis was performed using path analysis, by testing hypotheses using IBM SPSS 23. The results showed that partially lifestyle and merchandise assortment had a significant influence on purchase decision, but service quality did not significantly influence purchase decision. Meanwhile, simultaneous lifestyle, merchandise assortment and service quality significantly influence purchase decision through purchase intention as an intervening variable.